Efficacy Of Halobacterial- And Cyanobacterial Pigments As Photosensitizing Materials (Applied Biological Research, 2023)
In the present study, the photosensitizing activity of phycocyanin and bacterio rhodopsin pigments derived from Halobacterium and a cyanobacterium, isolated  from solar saltpan sediments of Cape Comorin coast of Tamil Nadu (India), was  assessed. Halobacterial strains were grown on halophillic agar and Zobell  marine agar; and pigmented bacteria identified on the basis of morpho biochemical characteristics. Cyanobacteria mats, gathered from the same  environment, were grown on BG11 medium, and identified on the basis of  morpho-biochemical characters as Oscillatoria sp., Spirulina sp. and Microcystis  Phycocyanin pigment was extracted from these cyanobacteria while bacteriorhodopsin pigment was extracted from Halobacterium sp. The pigments  were extracted by a centrifugation process, and characterised by HPLC and UV  spectroscopy. In addition, the photosensitization capacity of pigments was  evaluated using TiO2 thin film. The photosensitizing activity was assessed  through band gap energy study using UV spectral analysis which was confirmed  by FTIR and SEM analysis. Four probe tests were performed to measure the  resistivity and conductivity of halobacterial and cyanobacterial pigment-coated  TiO2 thin films.
Keywords: Bacteriorhodospin; conductivity; cyanobacteria; Halobacterium sp; pycocyanin; photosensitization; salt pan